2019
DOI: 10.1590/2318-0331.241920180147
|View full text |Cite
|
Sign up to set email alerts
|

COD removal from sucrose solution using hydrodynamic cavitation and hydrogen peroxide: a comparison between Venturi device and orifice plate

Abstract: The aim of the current study is to compare the chemical oxygen demand (COD) removal efficiency of a Venturi device to that of an orifice plate. The inlet pressure in the devices was optimized and the degradation kinetics was analyzed. In addition, the synergistic effect resulting from the combination between cavitation and H2O2 was investigated. An experimental apparatus was built to achieve these goals. A sucrose solution and an effluent from a sucrose-based soft drink industry were treated. Results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This outcome can be explained by the fact that the HC/ H2O2 combination generates more reactive species, reduces mass transfer resistance, and increases turbulence generation (RAUT-JADHAV et al 2013). Other authors have also reported pollutant degradation increase in case of HC combined with H2O2 (ALVES et al, 2019;JOSHI and GOGATE, 2019;SAXENA et al, 2018;MACHADO et al, 2020). It is observed that system efficiency is increased when cavitation is combined with the decantation phenomenon.…”
Section: Experimental Project and Analysis Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…This outcome can be explained by the fact that the HC/ H2O2 combination generates more reactive species, reduces mass transfer resistance, and increases turbulence generation (RAUT-JADHAV et al 2013). Other authors have also reported pollutant degradation increase in case of HC combined with H2O2 (ALVES et al, 2019;JOSHI and GOGATE, 2019;SAXENA et al, 2018;MACHADO et al, 2020). It is observed that system efficiency is increased when cavitation is combined with the decantation phenomenon.…”
Section: Experimental Project and Analysis Methodsmentioning
confidence: 93%
“…Hydrodynamic cavitation (HC) is one of the alternatives emerging as efficient to remove water pollutants (BATISTA; ANHÊ; GONÇALVES, 2017;ALVES et al, 2019;MACHADO et al, 2020). It is generated by liquid passage through physical constriction (cavitation chamber), such as an orifice plate and a Venturi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, degradation efficiency is significantly reduced at low oxidant concentrations. Alves et al (2019) used hydrodynamic cavitation to analyze COD reduction efficiency of an effluent whose main constituent was sucrose. Based on their results, 90% removal efficiency was observed when peroxide/sucrose molar ratio was equal to 20, cavitation time was 25 min and inlet pressure was 4.0 bar.…”
Section: Bromothymol Blue Degradationmentioning
confidence: 99%
“…The HC phenomenon has been applied in numerous applications of sanitary and environmental engineering (involving physical-chemical processes), from water treatment (DULAR et al, 2016;BAGAL;, wastewater containing pesticides (PATIL et al, 2014), drugs dissolved in water ZUPANC et al, 2013), effluent from tannery waste (SAXENA et al, 2018), effluent from soft drink industry (ALVES et al, 2019), to dye removal (RAJORIYA et al, 2017;RAJORIYA et al, 2018) and algae removal (BATISTA et al, 2017). In production processes there are reports over the use of HC ranging from the synthesis of biodiesel (MADDIKERI et al, 2014), pre-treatment of biomass (HILARES et al, 2017) to the production of nanoemulsion (CARPENTER et al, 2017).…”
Section: Introductionmentioning
confidence: 99%